A PEDESTRIAN STEP COUNTING PARAMETER DETECTION METHOD AIDED WITH ANGULAR VELOCITY INFORMAITON - WANG Ping; ZHANG GuangPeng; ZHANG YanShun; HUANG ShuFeng; YAO Juan (Jixie qiangdu)
In waist-worn pedestrian navigation systems, the peak detection method accuracy will be reduced when pedestrian carries on activities ups and downs in-situ such as stooped to and fro,squatting up and down. To compensate this error,a pedestrian step detection method aided with angular velocity is proposed based on the analysis on body waist motion feature. This method first extracts body’s forward angular velocity and lateral one to judge whether pedestrian walks ahead. Then peak signal of vertical accelerometer output is used to detect steps in common. In 27 experiments,which pedestrian walked certain steps and interference of activities ups and downs in-situ were brought in,the average accuracy rate of peak detection method and this method was 85. 8%,98. 84% respectively. Experimental results demonstrate that the proposed method can effectively reduce step detection errors generated by walking ups and downs in-situ with a high reliability.